2020
DOI: 10.1287/isre.2019.0880
|View full text |Cite
|
Sign up to set email alerts
|

When the Bank Comes to You: Branch Network and Customer Omnichannel Banking Behavior

Abstract: Banks today have been increasingly reducing their physical presence and redirecting customers to digital channels, and yet, the consequences of this strategy are not well studied. This research investigates the effects of banks’ branch network changes (i.e., branch openings and branch closures) on customer omnichannel banking behavior. Using a proprietary data set from a large commercial bank in the United States, this paper shows the asymmetric effects of branch openings and branch closures on customer omnich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 35 publications
0
22
0
1
Order By: Relevance
“…Our review demonstrates that the exploration of consumer responses to omnichannel stimuli has been in the forefront of consumer behaviour research in recent years (Du et al., 2018; Ieva & Ziliani, 2018; Juaneda‐Ayensa et al., 2016; Murfield et al, 2017; ; Park & Kim, 2019; Zhou et al., 2020). For instance, previous studies employed the Wixom & Todd model (Shen et al., 2018), Stimulus‐Organism‐Responses model (Zhang et al, 2018b) and the Engel et al’s model (Kang, 2018, 2019) to understand factors affecting the consumer decision making process within the specific context of omnichannel retailing.…”
Section: Research Findings and Analysismentioning
confidence: 95%
See 2 more Smart Citations
“…Our review demonstrates that the exploration of consumer responses to omnichannel stimuli has been in the forefront of consumer behaviour research in recent years (Du et al., 2018; Ieva & Ziliani, 2018; Juaneda‐Ayensa et al., 2016; Murfield et al, 2017; ; Park & Kim, 2019; Zhou et al., 2020). For instance, previous studies employed the Wixom & Todd model (Shen et al., 2018), Stimulus‐Organism‐Responses model (Zhang et al, 2018b) and the Engel et al’s model (Kang, 2018, 2019) to understand factors affecting the consumer decision making process within the specific context of omnichannel retailing.…”
Section: Research Findings and Analysismentioning
confidence: 95%
“…Shopping intention, purchasing and recommendation to use the omnichannel environment (e.g., word‐of‐mouth, online recommendation, reference) are the most common themes that emerged from the literature. A number of studies suggest various factors influencing omnichannel shopping intention (Juaneda‐Ayensa et al., 2016; Kang, 2019; Kazancoglu & Aydin, 2018; Park & Kim, 2019; Shi et al., 2020; ; Zhou et al., 2020), including connectivity, integration, consistency, flexibility and personalization (Shi et al., 2020). Omnichannel consumers’ showrooming and webrooming behaviours have been shown to positively affect their intention to develop user‐generated content (Kang, 2018).…”
Section: Research Findings and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The branch closure was found to significantly increase consumer churn of heavily physical store users of the video rental company (Soysal et al, 2019). The branch closure drives positive migration to digital banking, but after the last bank in the neighborhood closes, transactions in all channels decrease in the long run (Zhou et al, 2020). What's more, the branch open and closure would result in a branch network structure change in the neighborhood of a consumer.…”
Section: Channel Managementmentioning
confidence: 99%
“…In omnichannel retail, decisions on branch open and closure, channel launch and closure have received considerable attention from researchers (Bell et al, 2018;Soysal et al, 2019;Zhou et al, 2020 Kumar et al (2019a) found the branch open increases both online and offline product sales through store engagement and store return effect. However, Zhou et al (2020) found the branch open decreases online transactions in the short term while increasing online transaction in the long term, because consumers learn about the services the bank offers from the branch and probably migrate to online channel for the learned services. The branch closure was found to significantly increase consumer churn of heavily physical store users of the video rental company (Soysal et al, 2019).…”
Section: Channel Managementmentioning
confidence: 99%